Thinking Styles in students of UNMSM - Escurra Mayaute, Luis Miguel (2001)
This research deals about the thinking styles proposed by Sternberg, on Freshman students of the Universidad National Mayor de San Marcos (U. N.M. S. M). The participants were a random sample of 501 students, belonging to 19 schools of 5 academic areas of U.N.M.S.M. The results confirm the validity, the construct validity and the reliability of Stenberg 's short form Thinking Styles Questionnaire. The results show that the most frequent styles are the ones related to the judicial junction, the external scope and the hierarchic form on The Least frequent results are the oligarchic form, the local level and the conservative style. Considering academic areas there were statistical differences on the executive and the judicial junction; the monarchic, the hierarchic, the oligarchic and the anarchic forms; the global and local levels; the internal and external scope; the Liberal and conservative styles. Comparing by gender showed statistical significance leniency of male participants on the judicial function; the monarchic form; the global and local level; the external scope; and the Liberal and conservative style.